Exploring the standing barbell overhead press - Kroell, J.; Mike, J. (Strength and Conditioning Journal, 2017)
The purpose of this column is to explore the standing barbell overhead press (sbohp) in terms of its execution, musculature involved, potential benefits, practical applications, and its evolution. The sbohp is among the most elementary tests of upper body and overhead strength. Because of its removal as a contested barbell lift, general emphasis on the movement has declined slightly, but it is still widely implemented in a plethora of settings from recreational and professional sports performance to utility in rehabilitation.